Chest-worn Transmitarray Lens for Monitoring Heart Rate Variability with a Remote Self-Injection-Locked Doppler Radar - El Arif, Rezki; Su, Wei-Chih; Horng, Tzyy-Sheng; Wu, Chung-Tse Michael (IEEE MTT-S International Microwave Symposium digest, 2023)
This paper presents a transmitarray lens that can be worn on the chest to focus the radar beam towards a specific area of the heart for monitoring heart rate variability (HRV). The used Doppler radar is based on self-injection-locking (SIL) technology and was placed remotely from the monitored subject. In the experiment, the transmitarray lens was set up to concentrate the incident wave penetrating into the chest on the heart's tricuspid valve; thus, the accuracy of monitoring HRV can be greatly improved. The comparison of the interbeat interval (IBI) data between the proposed radar measurement and the conventional electrocardiogram (ECG) shows excellent agreement.